Comparative Genomic Analysis of Bacillus amyloliquefaciens and Bacillus subtilis Reveals Evolutional Traits for Adaptation to Plant-Associated Habitats - Zhang, Nan; Yang, Dongqing; Kendall, Joshua R. A.; Borriss, Rainer; Druzhinina, Irina S.; Kubicek, Christian P.; Shen, Qirong; Zhang, Ruifu (Frontiers in Microbiology, 2016)
Bacillus subtilis and its sister species B. amyloliquefaciens comprise an evolutionary compact but physiologically versatile group of bacteria that includes strains isolated from diverse habitats. Many of these strains are used as plant growth-promoting rhizobacteria (PGPR) in agriculture and a plant-specialized subspecies of B. amyloliquefaciens - B. amyloliquefaciens subsp. plantarum, has recently been recognized, here we used 31 whole genomes [including two newly sequenced PGPR strains: B. amyloliquefaciens NJN-6 isolated from Musa sp. (banana) and B. subtilis HJ5 from Gossypium sp. (cotton)] to perform comparative analysis and investigate the genomic characteristics and evolution traits of both species in different niches. Phylogenomic analysis indicated that strains isolated from plant-associated (PA) habitats could be distinguished from those from non-plant-associated (nPA) niches in both species. The core genomes of PA strains were more abundant in genes relevant to intermediary metabolism and secondary metabolites biosynthesis as compared with those of nPA strains, and they also possessed additional specific genes involved in utilization of plant-derived substrates and synthesis of antibiotics. A further gene gain/loss analysis indicated that only a few of these specific genes (18/194 for B. amyloliquefaciens and 53/688 for B. subtilis) were acquired by PA strains at the initial divergence event, but most were obtained successively by different subgroups of PA stains during the evolutional process. This study demonstrated the genomic differences between PA and nPA B. amyloliquefaciens and B. subtilis from different niches and the involved evolutional traits, and has implications for screening of PGPR strains in agricultural production.